2016
DOI: 10.1111/1365-2435.12630
|View full text |Cite
|
Sign up to set email alerts
|

Parental age influences offspring telomere loss

Abstract: Summary1. The age of the parents at the time of offspring production can influence offspring longevity, but the underlying mechanisms remain poorly understood. The effect of parental age on offspring telomere dynamics (length and loss rate) is one mechanism that could be important in this context. 2. Parental age might influence the telomere length that offspring inherit or age-related differences in the quality of parental care could influence the rate of offspring telomere loss. However, these routes have ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 60 publications
(126 reference statements)
3
59
1
Order By: Relevance
“…The father's early growth rate (and hence time taken to reach the marine phase) had an association in the later stages of development. We found no link between parental age and offspring telomere length in salmon, despite this previously being found to be one of the most pervasive parental effects on offspring telomere length across a range of taxa (e.g., Asghar et al, 2015;Broer et al, 2013;De Meyer et al, 2007;Heidinger et al, 2016). However, it may be the case that our relatively smaller sample size (in comparison to these other studies) did not allow enough power to statistically detect a parental age effect.…”
Section: Discussioncontrasting
confidence: 88%
“…The father's early growth rate (and hence time taken to reach the marine phase) had an association in the later stages of development. We found no link between parental age and offspring telomere length in salmon, despite this previously being found to be one of the most pervasive parental effects on offspring telomere length across a range of taxa (e.g., Asghar et al, 2015;Broer et al, 2013;De Meyer et al, 2007;Heidinger et al, 2016). However, it may be the case that our relatively smaller sample size (in comparison to these other studies) did not allow enough power to statistically detect a parental age effect.…”
Section: Discussioncontrasting
confidence: 88%
“…The first examined only 12 individual sand lizards ( Lacerta agilis ) and found that having older PAC predicted shorter TL (Olsson et al 2011). The second examined 204 European shag ( Phalacrocorax aristotelis ) chicks and found no association of TL with paternal age (Heidinger et al 2015). Here we examine whether the PAC-effect is evident in captive chimpanzees ( Pan troglodytes ), our closest living relatives.…”
Section: Introductionmentioning
confidence: 99%
“…A key question to be addressed is the extent to which RTL, especially in early life, reflects inheritance and parental effects (e.g. Asghar, Bensch, Tarka, Hansson, & Hasselquist, 2014;Becker et al, 2015;Heidinger et al, 2016). For example, parental age and quality may key variables that impact the telomere dynamics of offspring in the Seychelles warbler, and will be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%